1975
DOI: 10.1093/jaoac/58.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Size on the Biological Availability of Reduced Iron

Abstract: A sample of reduced iron was separated by air elutriation into several fractions based on particle size; and the relative biological values (RBVs) of 3 fractions containing fine, medium, and coarse particles were determined with rats and chicks, using diets containing either skim milk powder or casein as the major source of protein. The RBV of reduced iron for rats was shown to be dependent on particle size by curative and prophylactic assay procedures, with the source of protein having no marked effect. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Shah & Belonje (1973), for example, showed that the RBV of electrolytic Fe powder increased from 12 to 32 % when the proportion of particles below 10 mm was increased from 62 to 99 %. Further, Motzok et al (1975) demonstrated that decreasing particle size of CO-reduced Fe powders from 24 -40 mm to 7-10 mm increased RBV from 11 to 31 %. Fe absorption from ferric orthophosphate has also been shown to be dependent on particle size as RBV increased nearly 8-fold (from 6 to 46 %) when particle size was decreased from approximately 15 mm to below 1 mm (Harrison et al 1976).…”
Section: Discussionmentioning
confidence: 93%
“…Shah & Belonje (1973), for example, showed that the RBV of electrolytic Fe powder increased from 12 to 32 % when the proportion of particles below 10 mm was increased from 62 to 99 %. Further, Motzok et al (1975) demonstrated that decreasing particle size of CO-reduced Fe powders from 24 -40 mm to 7-10 mm increased RBV from 11 to 31 %. Fe absorption from ferric orthophosphate has also been shown to be dependent on particle size as RBV increased nearly 8-fold (from 6 to 46 %) when particle size was decreased from approximately 15 mm to below 1 mm (Harrison et al 1976).…”
Section: Discussionmentioning
confidence: 93%
“…Earlier studies have shown that solubility i.d.a. of poorly acid soluble compounds is related to particle SSA (Motzok and others 1975) and an increase in SSA (that is, decrease in particle size) can significantly improve solubility i.d.a., as seen for FePO 4 (Rohner and others 2007). Figure 3 shows the SSA of flame‐made nanostructured Fe 2 O 3 ‐based particles as a function of additive content.…”
Section: Resultsmentioning
confidence: 99%
“…However, low iron bioavailability of elemental powders relative to water-soluble compounds limit their nutritional value. Particle size reduction is an effective strategy for improving iron bioavailability from elemental powders [ 29 ]. Particle size reduction is inversely related to iron solubility at low pH, which has been shown to be the best in vitro predictor of iron bioavailability in humans [ 17 , 30 ].…”
Section: Discussionmentioning
confidence: 99%